Evaluacion de abonos orgánicos en la producción de maiz tusilla (zea mayz) en el recinto San Carlos, parroquia Sevilla cánton Cáscales, provincia de Sucumbíos - Verdezoto Naranjo, Raúl Emilio (2015)
The maize crop is of great importance in agricultural activity in our country and in the eastern region due to its use in food and feed; Therefore, in the present research developed in the campus of San Carlos Sevilla parish, the canton Cascales, Sucumbios province; They were developed and applied four types of solid manure in front of a witness in the maize variety tusilla. The objectives were; To evaluate the effect of organic fertilizers on crop yield tusilla corn (Zea mays), To determine the profitability of each of the treatments applied, To disseminate the results to farmers in the agricultural sector in the area of influence. For the test set land clearing was done, plot layout and proceeded to hoyado, composting and planting corn. The variables evaluated were: plant height, days to flowering, number of ears per plant, ear size, number of grains / ear and performance. Also, the direct costs for the determination of the B / C were recorded. The results obtained were significant for the variables plant height at flowering and performance; while in the variables: number of ears per plant, ear size and number of grains per ear, although they were not obtained varied numerically significant differences. Production costs were higher in the treatments where organic fertilizers and less used in the control, which contributed to the B / C ratio is greater in the control; however, it should consider improving the manured soils.